PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA BUKU ”MEMBACA ITU MENGASYIKKAN” DI TK PLUS AL BURHAN KECAMATAN BUARAN KABUPATEN PEKALONGAN - Labib Sajawandi; Anita Rosalina (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2020)
This study was designed to describe and analyze the increase in early reading skills using the media "Membaca Itu Mengasyikkan" at TK Plus Al Burhan, by analyzing the media application of books that use Early Childhood learning. The study was conducted in TK Plus Al Burhan in group B, the data collection method used observation, interviews, and documentation, the data analysis technique used descriptive qualitative. The application of the book "Membaca Itu Mengasyikkan" in TK Plus Al Burhan is as follows: Providing special time, classical techniques and individual techniques, Using the media of books "Membaca Itu Mengasyikkan", Providing a means of playing literacy. the advantage of this book is that learning to read will be more systematic and controlled so that parents at home can know until the development of children's reading skills. While the drawbacks / challenges are the need for caution in their application so that it is not even bad for children. development, information and measurement systems must be objective.